(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Female patients presenting in surgical emergency department often have an underlying gynaecological cause. The most common causes are ovarian pathologies such as cyst rupture or torsion, small gut perforation, gut adhesion and ureteric or urinary bladder injuries. These conditions may clinically resemble certain surgical causes of acute abdomen. Sometimes the diagnosis may only be confirmed per-operatively. Methodology: A total of 79 females who were operated during the six months study period at the surgical emergency department of Sir Ganga Ram Hospital, Lahore, for some gynaecological pathology were included in the study. Routine laboratory and clinical investigations were conducted in all cases. The clinical history and diagnosis were recorded. Results: The age range for patients was 15 to 47 years (mean age 29.20 + 7.2). Sixty-three patients (79.7%) were married and 16 (20.3%) were unmarried. Among these patients, 21.5% were nulliparous, 38% were primiparous and 40.5% were multiparous. The most common symptoms were nausea and vomiting (68.4%), peritonitis (63.3%) and fever (50.6%). Shock was observed only in 6 patients (7.5%). The most common etiology was ileal perforation (22.8%), rupture or torsion of ovarian cyst (20.3%) and adhesion of gut with uterus or ovaries (17.7%). Mortality was observed in 3 (3.3%) patients. Conclusion: Gynaecological conditions requiring surgical management are commonly encountered on surgical emergency floor. The post-graduate trainees working in surgical and gynaecological emergencies must be trained to deal with such emergencies.